Global logistics and supply chain management - Mangan, John 1968-; Lalwani, Chandra (Chichester, United Kingdom Wiley, 2016)
Think of the many different products and services that are purchased and consumed each day how do they reach the end-user? What does this cost? What happens when something goes wrong?
Revised edition of the authors' Global logistics and supply chain management, 2012.
Includes bibliographical references and index.
Keywords: Business logistics